2022
DOI: 10.3389/fmed.2022.935961
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin exercise: A potential promising therapy toward osteoporosis

Abstract: PurposeBaduanjin (BDJ) exercise is a traditional exercise that combines breathing, body movement, meditation and awareness to help delay the onset and progression of senile degenerative musculoskeletal diseases, such as osteoporosis (OP). The aim of this meta-analysis is to evaluate the efficacy of BDJ exercise, and preliminarily infer its effective mechanism in the treatment of OP.MethodsWe identified relevant randomized controlled trials (RCTs) through eight databases, and compared BDJ exercise with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…45 Ca and phosphorus in the blood reflect the physical structure of the bones. 46 Ca is an important mineral in the human body, of which 99% is found in the bones and teeth, and the remaining 1% is distributed in the blood, nerves, and various soft tissues. 47 Properly increased Ca content is beneficial to calcium deposition in bone, while excessively increased Ca content may be deposited in the soft tissues such as blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Ca and phosphorus in the blood reflect the physical structure of the bones. 46 Ca is an important mineral in the human body, of which 99% is found in the bones and teeth, and the remaining 1% is distributed in the blood, nerves, and various soft tissues. 47 Properly increased Ca content is beneficial to calcium deposition in bone, while excessively increased Ca content may be deposited in the soft tissues such as blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…ALP is a measure of bone formation and transformation, since release into the blood disrupts estrogen production, whereas elevated serum ALP activity reflects the activity of bone cell metabolic processes 45 . Ca and phosphorus in the blood reflect the physical structure of the bones 46 . Ca is an important mineral in the human body, of which 99% is found in the bones and teeth, and the remaining 1% is distributed in the blood, nerves, and various soft tissues 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have applied Yoga, Pilates, Tai Chi, and Ba Duan Jin to patients with osteoporosis and have obtained various results. Although many studies have reported the effectiveness of pain relief (Oksuz & Unal, 2017; Sun et al, 2021), there were still negative results reported by researchers (Grahn Kronhed et al, 2020). Exercising the wrong way could cause adverse consequences (Sluka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Then take the lumbar spine as the axis to drive their four limbs movement, while alternately change the muscle tension and relaxation at different parts of the body. At same time, the mind, body, and breath are required to be smooth and unstrained ( 26 ). Numerous studies have already proven that Baduanjin is a popular community exercise to promote health in China, and especially suitable for older adults ( 13 , 17 , 27 ).…”
Section: Discussionmentioning
confidence: 99%